2019
DOI: 10.1016/j.jid.2019.03.904
|View full text |Cite
|
Sign up to set email alerts
|

828 Dermatopathologist-level classification of skin cancer with deep neural networks at multi-magnification

Abstract: Conventional monotherapies only benefit a minority of melanoma patients while combined immunotherapy exhibited extremely high rates of treatment-related adverse events. Herein, we created a multifunctional and immunogenic nanoplatform, AuNR@mSiO 2 @DOX-Cu x S-PEG, which integrating photothermal properties of gold nanoparticles, photodynamic properties of CuxS and chemotherapy into a single nanoplatform. Upon near-infrared laser irradiation (NIR), the Cu x S were uncapped and triggered chemotherapy drugs releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…In these methods, various features (preferably those which are important for a particular scenario) are extracted through either deep learning or neural networks by feeding large datasets along with the corresponding classification labels [8,9]. Diagnostic convolutional neural networks (CNN) have matched or exceeded the expected ability of field experts in several pathological image recognition tasks [10,11] particularly for the diagnosis of the lung and breast cancer at the earliest possible state [12,13]. Likewise, in the skin pathology recognition task, Hekler et al [14] have demonstrated the pathologist-level classification of malignant melanomas versus benign nevi using a pretrained ResNet50 CNN.…”
Section: Introductionmentioning
confidence: 99%
“…In these methods, various features (preferably those which are important for a particular scenario) are extracted through either deep learning or neural networks by feeding large datasets along with the corresponding classification labels [8,9]. Diagnostic convolutional neural networks (CNN) have matched or exceeded the expected ability of field experts in several pathological image recognition tasks [10,11] particularly for the diagnosis of the lung and breast cancer at the earliest possible state [12,13]. Likewise, in the skin pathology recognition task, Hekler et al [14] have demonstrated the pathologist-level classification of malignant melanomas versus benign nevi using a pretrained ResNet50 CNN.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 4,888 specimens were included, of which at least 2,715 were melanoma specimens. The diagnostic entities within the datasets varied between studies, with some only containing melanoma deposits 12,21,[24][25][26]33 and others containing more than one pathology 10,11,22,[27][28][29][30][31][32] .…”
Section: Resultsmentioning
confidence: 99%
“…There was between-study variation in terms of intended use of the IA. Most studies focused on a binary classification task, with some focussing on detection and localisation of melanoma deposits in WSIs containing melanoma (melanoma versus not melanoma) 12,25,26,32 and others performing diagnostic classifications including melanomas versus naevi 11,22,31 and primary melanoma versus metastatic melanoma 33 . Five studies addressed more complex classifications into three or more diagnostics entities 10,23,[28][29][30] .…”
Section: Study Characteristics Study Characteristics Are Presented Inmentioning
confidence: 99%
See 2 more Smart Citations